2016
DOI: 10.1371/journal.pone.0152789
|View full text |Cite
|
Sign up to set email alerts
|

The Proton-Sensing G-Protein Coupled Receptor GPR4 Promotes Angiogenesis in Head and Neck Cancer

Abstract: Squamous cell carcinoma of the head and neck (SCCHN) is an aggressive disease with poor survival and is the sixth most common cancer worldwide. Gastroesophageal reflux is a common event in SCCHN patients. GPR4 is a proton-sensing G-protein coupled receptor, which can be activated by acidosis. The objective of this study was to explore the role of GPR4 in acid exposure and tumor angiogenesis in SCCHN. In this study, we confirmed that overexpressing GPR4 in SCCHN cells could increase the expression and secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 45 publications
(49 reference statements)
2
53
0
Order By: Relevance
“…Trypsinized hemangioma cells were harvested and resuspended (1×10 4 cells/100 µL medium), seeded into matrigel, then incubated at 37°C for 6 h. Tube structures were inspected under an inverted light microscope (200× magnification). The images were quantified using the Image-Pro Plus 6.0 software from Media Cybernetics (USA), as previously described ( 13 ). The quantified values are reported as the fold of control.…”
Section: Methodsmentioning
confidence: 99%
“…Trypsinized hemangioma cells were harvested and resuspended (1×10 4 cells/100 µL medium), seeded into matrigel, then incubated at 37°C for 6 h. Tube structures were inspected under an inverted light microscope (200× magnification). The images were quantified using the Image-Pro Plus 6.0 software from Media Cybernetics (USA), as previously described ( 13 ). The quantified values are reported as the fold of control.…”
Section: Methodsmentioning
confidence: 99%
“…nonlinear and possibly degenerate diffusion 7 by a slight abuse of definition we will call y an internal variable, which stresses out the fact that its dynamics is acting on the faster, subcellular scale 8 usually proton dynamics refers to their shuttling across the cell membrane by several transporters like NHE (Na + and H + exchanger), NDBCE (Na + dependent Cl-HCO 3 exchanger), MCTs (monocarboxylate transporters) and AE (Cl-HCO 3 anion exchanger), however there have also been investigated cell receptors -so-called proton sensing-which can be activated by acidosis, see e.g., [14,34,55] …”
Section: B)mentioning
confidence: 99%
“…Certain studies have demonstrated the role of GPR4 in the process of angiogenesis. Jing et al (9) revealed the promotion of angiogenesis by GPR4 in head and neck cancer, and Ren et al (10) reported that the overexpression of GPR4 may be required for angiogenesis in epithelial ovarian carcinomas. The expression of VEGFR2 and the angiogenic response to VEGF was found to be decreased in GPR4-deficient mice (11).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that GPR4 plays an important role in angiogenesis. Furthermore, certain studies have demonstrated the ability of GPR4 to induce angiogenesis in ovarian cancer and squamous cell carcinoma of the head and neck (SCCHN) (9,10). In ovarian cancer, the expression level of GPR4 is positively correlated with the microvessel density (MVD) of vascular ECs, which is not observed in benign ovarian tissues (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation